Literature computer program among primary school learners - Abd Rahim, Normaliza (Sakarya University, Sakarya, 2013)
This study focuses on the use of computer in learning Malay literature. The objectives of the study were to identify and discuss the basic knowledge and views towards the Malay literature program by using the computer. The samples of the study consisted of 10 subjects who volunteered from Malay language class. They were nine-year-old male and female students. The study was carried out in one primary school in Malaysia. The subjects were given a task in the Malay language program, which consisted of various Malay literature genres, such as short story, poem, quatrain and drama. The study was carried out for one week and the subjects were interviewed and observed throughout. Their views were selected based on the purpose of the study. The results of the study revealed that the subjects were able to answer the questions from the given task. They managed to offer their views about the program and managed to learn new vocabulary. It is hoped that a future study will focus on other technology in learning Malay literature.